Pengaruh Kualitas Pelayanan Kesehatan terhadap Kepuasan Pasien di Rumah Sakit Umum Bina Sehat - Khoirunnisa, Sarah; Ramadhika, Alda (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
This study aims to analyze the impact of healthcare service quality on patient satisfaction at Bina Sehat General Hospital. The research uses a quantitative approach with a survey method. Data were collected from a sample of 88 patients using a structured questionnaire. The dimensions of healthcare service quality examined include tangibility, reliability, responsiveness, assurance, and empathy. The results of the regression analysis indicate that healthcare service quality significantly influences patient satisfaction. Among the dimensions, assurance and empathy show the strongest positive correlation with patient satisfaction. The findings suggest that improvements in these areas are likely to enhance overall patient satisfaction. These efforts are expected to not only improve patient satisfaction but also contribute to the hospital’s reputation and patient loyalty.